Abatement of Cr(VI) rich wastewater in a novel multistage External Loop Airlift Reactor using acidified activated carbon. (3rd December 2009) - Mohanty, Kaustubha; Das, D.; Biswas, M.N.
In the present investigation, a multistage External Loop Airlift Reactor (ELALR) has been used for the treatment of Cr(VI) rich wastewater using acidified activated carbon as the adsorbent. The multistaging has been achieved by hydrodynamically induced continuous bubble generation, break-up and regeneration. The continuous rupture and bursting of bubbles creates localised turbulence and recirculation, which helps in faster transfer of Cr(VI) to the active sites of the solid adsorbents. The effect of different process parameters like contact time, adsorbent dose, superficial gas velocity on the removal of Cr(VI) was studied and it was found that the removal time for this system is quite lower as compared with simple batch adsorption systems. The kinetic data were fitted to the models of intra-particle diffusion, pseudo-second-order, and Lagergren, and followed more closely the Lagergren pseudo-first-order model.